Movimentos de construção de sentidos e suas rizomatizações no curso Wanna Talk?!: um estudo sobre multimodalidade crítica em aulas de inglês - (:unkn) unknown (Universidade Estadual de Goiás, 2022)
The purpose of this study is to reflect on issues raised in the online course called "WANNA TALK?! Leitura, debate e produções multimodais em aulas de inglês” for learners entering and exiting the State University of Goiás (UEG). The course aimed at: reading multimodal texts; raising problematizations and debates about topics defined/suggested by me and the agents; producing multimodal texts from the discussions in class and collaboratively building material for mediation of the meetings (remote via Google Meet). The course made it possible to create empirical material so that, in this study, I can understand which processes of meaning production and rhizomatization were mobilized by the English learners during the discussions and how the expansion of repertoires (CANAGARAJAH, 2007, 2011), the use of digital tools and text/world readings could be explored and perceived when we look at multimodality (VAN LEUWEEN, 2005; KRESS, 2010; SOARES, 2021, among others) and the literacies that could be problematized through these readings. This study follows a post-critical approach (PARAÍSO, 2004; LATHER; ST. PIERRE, 2013) in research. I conducted my study under this approach because, like post-critical researches, I aimed to analyze the different ways in which texts are represented to promote the agency and subjectivity of the agents. Above all, with this research approach, I could see how meanings were constructed from the worldviews of English learners and my own, having the opportunity to (un/re)construct myself as a researcher and language educator. The course was taught by me via Google Meet due to the remote classroom setting we have experienced since the outbreak of the Covid-19 pandemic in March 2020. Didactic paths were rethought throughout the course. The constructions of the talks were observed considering the rhizome metaphor (DELEUZE; GUATTARI, 1995), since the relations occurred in a non-linear way. Thus, I tried to observe where we were, from where the connections emerged, and how the debates followed. The course, as empirical material raised for this research, was studied based on readings such as those by Masny (2006, 2009, 2010), Kress (2010), Canagarajah (2011), Ferraz and Tomizuka (2021), Soares (2021), among other authors. Finally, through the discussions recorded on video by Google Meet, I could build with the agents several readings of texts and the world, developing critical literacy (JORDÃO, 2007, MENEZES DE SOUZA, 2011) and discussing the critical multimodal literacies that could be engaged in our practices. I mean, in addition to observing how the agents' improvement has flowed in terms of speaking/listening constructions in the English language, I also analyzed to what extent knowledge was resignified and how worldviews were broadened through multimodal texts readings.
Meaning construction movements and their rhizomatizations in the Wanna Talk?!Course: a study of critical multimodality in English classes
Keywords: Letramentos multimodais; Multimodalidade crítica - Aulas de inglês; Perspectivas críticas - Aulas de inglês; Multimodal literacies; Critical multimodality - English classes; Critical perspectives - English classes; CIENCIAS HUMANAS::EDUCACAO